2022
DOI: 10.22219/raden.v2i2.23232
|View full text |Cite
|
Sign up to set email alerts
|

Development of articulate storyline learning media to improve biology learning outcomes for junior high school students

Abstract: Learning media is an important key to the success of learning to lead to student interaction with learning resources so that goals can be achieved, one of which is in biology lessons in junior high school. The purpose of this study was to produce a product in the form of learning media using Articulate Storyline software, in which to determine an increase in student learning outcomes in class VIII Junior High School (SMPN) 5 Malang. This study uses Research and Development (R&D) research by using the Borg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 8 publications
(12 reference statements)
0
4
0
2
Order By: Relevance
“…Moreover, this research seeks to enhance teachers' knowledge and understanding of effective learning media by showcasing the potential and benefits of Articulate Storyline. By building upon the findings of previous studies, this research contributes to the advancement of instructional design and promotes the adoption of innovative and interactive approaches in educational settings; some relevant studies can be found (Ariani, 2020;Hadza et al, 2020;Istyadji et al, 2022;Jubaerudin et al, 2021;Nasution & Darwis, 2021;Nissa et al, 2021;Nugroho & Arrosyad, 2020;Rianto, 2020;Saadah et al, 2022;Yolanda et al, 2022).…”
Section: Introductionmentioning
confidence: 92%
“…Moreover, this research seeks to enhance teachers' knowledge and understanding of effective learning media by showcasing the potential and benefits of Articulate Storyline. By building upon the findings of previous studies, this research contributes to the advancement of instructional design and promotes the adoption of innovative and interactive approaches in educational settings; some relevant studies can be found (Ariani, 2020;Hadza et al, 2020;Istyadji et al, 2022;Jubaerudin et al, 2021;Nasution & Darwis, 2021;Nissa et al, 2021;Nugroho & Arrosyad, 2020;Rianto, 2020;Saadah et al, 2022;Yolanda et al, 2022).…”
Section: Introductionmentioning
confidence: 92%
“…Articulate Storyline dapat memberikan perubahan yang disambut baik di kelas dengan membuat materi pelajaran yang lebih menarik bagi siswa dan lebih mudah disampaikan oleh pendidik (Firdawela & Reinita, 2021). Pengembangan media dengan Articulate Storyline dapat membuat materi pembelajaran tersampaikan dengan baik sekaligus memudahkan pengguna untuk mengoperasikan media dan dapat menarik perhatian siswa (Husna & Fajar, 2022;Saadah, Hadi, Budiyanto, Rahardjanto, & Hudha, 2022;Yolanda, Winarni, & Yulisetiani, 2022). Mengingat keterbatasan jumlah waktu, ruang, dan kemampuan guru dalam menjelaskan materi, maka dengan penggunaan media interaktif ini dapat memaksimalkan penyampaian guru ke siswa khususnya dalam mata pelajaran PPKn berbasis kearifan lokal Tri Hita Karana kelas V Sekolah Dasar.…”
Section: Pendahuluanunclassified
“…The Articulate Storyline application has many features with a combination of slides, videos, flash (swf) and animated characters in one. Media Articulates Storylines have a variety of interesting templates so they can create a learning media project easily and in a short time (Jais & Amri, 2021;Saadah et al, 2022).…”
Section: Introductionmentioning
confidence: 99%